2013
DOI: 10.1016/j.radonc.2013.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Motion-specific internal target volumes for FDG-avid mediastinal and hilar lymph nodes

Abstract: Background and Purpose To quantify the benefit of motion-specific internal target volumes for FDG-avid mediastinal and hilar lymph nodes generated using 4D-PET, vs. conventional internal target volumes generated using non-respiratory gated PET and 4D-CT scans. Materials and Methods Five patients with FDG-avid tumors metastatic to 11 hilar or mediastinal lymph nodes were imaged with respiratory-correlated FDG-PET (4D-PET) and 4D-CT. FDG-avid nodes were contoured by a radiation oncologist in two ways. Standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Furthermore, the nodal volume delineated on PET tends to be larger than that delineated on CT, which was felt to be possibly caused by respiratory motion. This was corroborated in a study on 4D-PET-based nodal disease delineation ( 38 ). As shown in this study, a 3D nodal internal target volume (ITV) expansion of over 1 cm is required to cover 91% of the lymph nodes while accounting for respiratory motion.…”
Section: Delineation Of Nodal Disease On Petsupporting
confidence: 58%
“…Furthermore, the nodal volume delineated on PET tends to be larger than that delineated on CT, which was felt to be possibly caused by respiratory motion. This was corroborated in a study on 4D-PET-based nodal disease delineation ( 38 ). As shown in this study, a 3D nodal internal target volume (ITV) expansion of over 1 cm is required to cover 91% of the lymph nodes while accounting for respiratory motion.…”
Section: Delineation Of Nodal Disease On Petsupporting
confidence: 58%
“…Two separate studies found spatial and contour disparities between 3D PET‐CT and 4D‐CT MIP ITVs, concluding that neither can replace the other in terms of ITV delineation 221,222 . Lamb et al 223 also demonstrated the improvement of ITV definition from 4D‐PET for tumor motion in the hilar and mediastinal regions over CT alone, due to the similar tissue density between tumor and surrounding normal tissues in this area. Their study proved that a uniform margin expansion from 3D PET is not adequate for ITV determination and in fact the asymmetric and appropriate margin expansion derived from 4D‐PET could not just improve target dose coverage, but also better spare surrounding healthy lung.…”
Section: Determining the Internal Target Volume (Itv)mentioning
confidence: 99%
“…The hitherto accumulated data accounted for in this review have however been considered robust and convincing enough for clinical societies to recommend PET/CT based dose planning for lung cancer (EORTC, NCCN, IAEA) [40,48,49]. In addition PET/CT for dose planning permits further development with dose painting of areas more prone for relapse [50,51] and motion adapted treatment with 4DPET [52].…”
Section: Discussionmentioning
confidence: 92%